Handbook of tourism economics analysis, new applications, and case studies - Tisdell, C. A. (Clement Allan) (World Scientific, 2013)
[This book] provides an up-to-date, concise and readable coverage of the most important topics in tourism economics. It pays attention to relevant traditional topics in tourism economics as well as exciting emerging topics in this field - topics which are expected to be of continuing importance. In doing this, it takes account of advances in economic thought, analysis and applied methods. Contributions provide applications of economic analysis to tourism policy and constructive assessment of contemporary thought about tourism economics. The handbook includes several in-depth case studies such as the contribution of tourism to economic development in selected countries including China, India, Japan and Australia, Portugal and Fiji. Coming from diverse countries (both industrialised and developing) and established in the field of tourism economics, travel and management, many of the contributors have been consultants to governments, private organisations, and international bodies, including the UN World Tourism Organisation, the OECD and UNEP. Experts contributing to this volume include the President of the International Association of Tourism Economics, as well as its Secretary-General, the Secretary-General of the Tourism Research Centre (Association of Tourism Research Institutes), the Founder-Fellow of the International Academy for the Study of Tourism and the former Director of the UK's Centre for Social and Economic Research on the Global Environment (CSERGE).